Flash Card Media To Improve Learning Outcomes Of Science Material On Cultural Diversity - Isnaeni, Lutfia Septinur; Prasetyaningtyas, Fitria Dwi (LPPM Undiksha, 2024)
Many students still do not understand science learning due to the use of inappropriate learning models or learning media, which impacts low learning outcomes. This research aims to develop Flash Card Media to Improve Learning Outcomes for Science Material on Cultural Diversity. This type of research is development research or Research and Development (R&D). The model used to develop media is ADDIE. The population in this study was all 20 grade IV elementary school students. The samples taken in this research were all 20 students. The research subjects are learning media experts and learning materials experts. The methods used to collect data are test and non-test methods. The instruments used to collect data were questionnaires and test questions. The techniques used to analyze the data are qualitative and quantitative descriptive analysis and the n-gain test. The research results show a real difference in the average pretest and posttest after implementing Flash Card Media in small-group and large-group trials. The N-gain results show that the increase in pretest to posttest scores is in the medium or high effectiveness criteria. It was concluded that Flash Card Media can improve students' science learning outcomes. Research implications Flash Card media can be used in learning.